Electrical and Electronic Measurements - ROUABHI Riyadh (Mohamed BOUDIAF University of M'sila, 2025)
This practical workbook (PW Electrical and Electronic Measurements) is intended for students in the second year of their bachelor's degree (Electrotechnics) at the Mohamed Boudiaf University in M'sila, Algeria. Its aim is to provide them with a working document that will enable them to validate the concepts taught in the lectures and tutorials on electrical and electronic measurements and to facilitate their practical application in experimental manipulations. It will also enable them to acquire the necessary know-how to use the equipment and the different measuring instruments used correctly and to gain a good understanding of the methods used. For this reason, the preparation of the practical work must be taken seriously and be the subject of particular attention on the part of the students, in order to obtain the maximum benefit from it without damaging the equipment placed at their disposal. All the sections presented in this document were carried out at the Bidaghogic Electronics Laboratory of the Mohamed Boudiaf University in M'sila.
Keywords: Resistance measurement; Inductance measurement; Capacity measurement; Phase shift measurement.